Decarbonising the residential heating sector: A techno-economic assessment of selected technologies. (15th October 2022) - Huckebrink, David; Bertsch, Valentin
Abstract: Decarbonising the residential heating sector through electrification can add to the existing flexibility demands in the electricity sector arising from spatio-temporal mismatches in supply in demand. Heat demand peaks during winter require seasonal flexibility, since solar availability is at its minimum, while uncontrolled scheduling of heating appliances requires short term flexibility. However, scheduling appliances optimally and seasonal energy storages can deliver short and long term flexibility by temporarily increasing indoor room temperatures in the short term, and hydrogen generation through electrolysis in the long term. Furthermore, waste heat of fuel cells for power supply coincides with heat demand during winter. Therefore, a techno-economic assessment of different heat provision technologies and refurbishments is performed with a building model implementing flexible heat demand. The model can invest in and schedule different appliances and thereby control the indoor temperature within given boundaries. Emission reductions are then applied and sensitivity analyses for indoor temperatures and H2 prices are performed. The results show that using a combination of solar PV, heat pumps, electrolysers and fuel cells is more cost-efficient than refurbishments. Hydrogen combustion is only used when hydrogen prices fall below gas prices, or when the lower indoor boundary temperature is above 23 °C. Highlights: A thermal building model is implemented in an energy systems modelling framework. Controllable indoor temperature allows the model to flexibly meet thermal demand. A variety of technologies including seasonal energy storage are implemented. Techno-economic analyses are performed with different emissions reductions.